2023
DOI: 10.1111/1759-7714.14880
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib combined with bevacizumab as the first‐line treatment in non‐small cell lung cancer patients with brain metastasis harboring epidermal growth factor receptor mutations

Abstract: Background The efficacy and safety of osimertinib combined with bevacizumab in non‐small cell lung cancer (NSCLC) patients with brain metastasis harboring epidermal growth factor receptor (EGFR) mutations have not been fully studied. Methods Treatment‐naïve NSCLC patients with brain metastasis harboring EGFR‐activating mutations were treated with osimertinib 80 mg oral daily and bevacizumab 15 mg/kg intravenously on day 1, repeated every 21 days, until disease progression, intolerable toxicity, or death. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(80 reference statements)
0
3
0
Order By: Relevance
“… 38 , 39 In addition, several studies have shown that bevacizumab has promising results in NSCLC patients with brain metastases. 38 , 40 42 In addition, we performed subgroup analyses of cancer types and brain metastases between the AT and non-AT groups and found that there was no significant difference in COVID-19 outcomes between the two groups ( Figure 6 ). Thus, although the ratio of cancer types and brain metastases was not balanced between the two groups, it had no significant effect on the outcome of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 In addition, several studies have shown that bevacizumab has promising results in NSCLC patients with brain metastases. 38 , 40 42 In addition, we performed subgroup analyses of cancer types and brain metastases between the AT and non-AT groups and found that there was no significant difference in COVID-19 outcomes between the two groups ( Figure 6 ). Thus, although the ratio of cancer types and brain metastases was not balanced between the two groups, it had no significant effect on the outcome of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clinical studies have shown promising activity against central nervous system metastases from combination modality. 27 , 28 Given these thoughts, we conducted a pooled analysis based on BM. The results showed that the combination treatment yielded a mild trend of better PFS in those patients with BM (HR = 0.91, 95% CI: 0.46–1.77), though not reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…And non‐small cell lung cancer (NSCLC) is the main type of cancer in lung cancer, accounting for ≈85–90% of all cases. [ 1 , 2 , 3 , 4 ] For radical surgical treatment of lung cancer, only a small number of patients diagnosed with early lung tumors can accept. Moreover, the risk of postoperative recurrence is high.…”
Section: Introductionmentioning
confidence: 99%